Relationship between facebook usage and attitude with facebook addiction among Malaysian female university students - Syed Zainudin, Sharifah Sofiah (2013)
Facebook is one of the most popular social networking website for female university students to interact and socialize with the others online. However, the excessive use of Facebook leads to the phenomenon of Facebook addiction which is now taking its toll especially among Malaysians. Compared to male university students, Facebook has the potential to negatively affect female students’ daily life more at large. Despite the popularity of Facebook, there has been very little research delving into the problem of Facebook addiction among female university students in Malaysia. This research henceforth aims to explore the relationship between female students’ Facebook usage patterns, their attitudes and motives using Facebook and their correspondence with Facebook addiction. This study employs the Technology Acceptance Model (TAM) and Uses and Gratifications Theory (U&G) in the examination of the attitudes and motives for the students’ use of Facebook. This study adopts the quantitative research method by using questionnaire surveys as the research instrument for data collection. Convenience sampling technique is also applied to the sample selection of the respondents. A self-administered questionnaire was distributed to a total of 380 female students from Universiti Kebangsaan Malaysia (UKM) and Universiti Tenaga Nasional (UNITEN). The data collected were then analyzed with a computer software that is the Statistical Package for Social Science (SPSS version 19.0). This research also conducts a number of other statistical procedures in the survey which include normality test, descriptive analysis, correlation and regression test. The findings of this study reveal that there are positive and significant associations between the female students’ Facebook usage patterns, their attitudes and motives for Facebook use with Facebook addiction. Additionally, the findings indicate that the combination of hours per day, days per week, perceived usefulness, passing-time, entertainment, companionship and social interaction contribute more to Facebook addiction among female university students. It is also found that the hour per day Facebook use is the major contributor to the level of Facebook addiction among female university students. It can be also concluded from the research that a huge number of female university students are highly addicted to Facebook.